Mistakes Made by Students While Posing Problems for Equations Containing Algebraic Fractional Expressions - Mehtap Tastepe; Huseyin Bahadir Yanik (Anı Publishing, 2023)
Conceptual and procedural knowledge has historically been one of the most discussed subjects in mathematics. In this study, errors in equations including algebraic fractional expressions were examined to determine where ninth-grade students in their comprehension of these expressions. The study employed a holistic multiple-case strategy, and the gathered data were evaluated using content analysis. The results indicate that students made the most mistakes with the definitions of quotient and fraction-whole. Certain sorts of errors in the job are applicable to all fraction interpretations, while others appear to be fraction-specific. Depending on the type of fraction, the mistake circumstances varies.